DevOps for media and entertainment : accelerate your digital transformation through automation, monitoring, and the cloud - Irani, Zubin; Cipes, Brandon (O'Reilly Media, 2017)
Media and Entertainment (M & E) businesses are struggling with digital transformation on a scale far more dramatic than any other industry. For companies whose business is movies, music, gaming, TV, radio, or publishing, software is no longer just a tool. It's now the main product. With this report, you'll learn why DevOps--the collaborative relationship between software development and IT operations--is indispensable if your M & E business is to thrive in this new environment. Authors Zubin Irani and Brandon Cipes of cPrime show you how to adopt DevOps tools, methods, and processes for building and operating platforms that deliver content to viewers, listeners, and players wherever they are, on any device, at any time. You'll examine the key components of a DevOps transformation, and discover how DevOps practices will help you keep up with the pace of technological change, consumer expectations, and your competitors. Understand why DevOps is first and foremost a people issue Take a deep dive into DevOps components: continuous integration, continuous delivery, cloud infrastructure, testing, and monitoring Achieve true efficiencies in speed to market, scalability, and the ability to innovate better and faster Explore case studies of how Disney, Associated Press, Sony, Discovery Communications, News Corp, and Netflix successfully adopted DevOps Learn a process for undertaking your DevOps transformation by starting small with just one team In 2009, new media upstart Flickr presented the first case study of DevOps in action at O'Reilly's Velocity conference. Now, DevOps is essential for every M & E business. Get a copy of this report and discover how to get your company started.